Mediasi Ganda Customer Engagement dan Innovation Capability pada Hubungan Digital Leadership terhadap Business Performance Perusahaan Jasa di Kota Balikpapan - Ribka Patta; Gusmawati Gusmawati; Agus Rahayu; Hery Eko Prastiyo; Syahril Hasan (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of digital leadership on business performance through customer engagement and innovation capability in service companies in Balikpapan City. The study used a quantitative approach with a survey method on 96 respondents selected using a purposive sampling technique. Data collection was carried out through direct and online questionnaires, then analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the help of the SmartPLS application version 4.0. The results showed that digital leadership did not significantly influence business performance. Conversely, digital leadership had a positive and significant effect on customer engagement and innovation capability. Furthermore, customer engagement did not significantly influence business performance, while innovation capability had a positive and significant effect on business performance. This study also found that customer engagement was unable to mediate the influence of digital leadership on business performance, while innovation capability was able to mediate the relationship positively and significantly. The research findings indicate that the success of a service company's digital transformation is more influenced by the organization's ability to create innovation than simply building customer engagement. This research provides theoretical contributions in the development of Dynamic Capability Theory and Resource-Based View (RBV), as well as providing practical implications for service companies in improving innovation capability to support business performance in the digital transformation era.